Catalytic Intramolecular Aminofluorination, Oxyfluorination, and Carbofluorination with a Stable and Versatile Hypervalent Fluoroiodine Reagent** - Yuan, Weiming (Angew Chem Int Ed Engl, 2015)
Application of a fluoroiodine analogue of the Togni reagent was studied in fluorocyclization reactions. In the presence of a transition-metal catalyst the applied fluoroiodine reagent can be used for aminofluorination, oxyfluorination, and carbofluorination reactions. The described procedure has a very broad synthetic scope for preparation of functionalized hetero- and isocyclic compounds having a tertiary fluorine substituent.